Pengaruh Brand, Packaging, Dan Price Terhadap Keputusan Pembelian Ice Cream Mixue Airlangga Di Kota Mataram - Haerunisah; Hj. Erviva Fariantin; Putri Reno Kemala sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of brand (X1), packaging (X2), and price (X3) on purchasing decisions (Y) of Airlangga Mixue ice cream in Mataram City. This type of quantitative research with an associative approach. The sampling technique used in this study is the Non-Probability Sampling technique. The total sample taken was 100 consumers who had purchased Airlangga Mixue Ice Cream in Mataram City. The analytical method used in this research is multiple linear regression analysis method. The test results show that partially the influence of brand, price has a significant effect on purchasing decisions, while packaging has no significant effect on purchasing decisions of Mixue Airlangga ice cream in Mataram City